Sarcolemmal Alterations in Unloaded Rat Heart after Heterotopic Transplantation - Makino, Naoki; Ganguly, Paul; Elimban, Vijayan; Dhalla, Naranjan S. (International Journal of Angiology, 2018)
Following heterotopic transplantation, the rat heart undergoes atrophy and exhibits delayed cardiac relaxation without any changes in contraction and systolic Ca2+ transients. Furthermore, the sarcoplasmic reticular Ca2+ uptake and release activities were reduced and Ca2+ influx through L-type Ca2+ channels was increased in the atrophied heart. Since Ca2+ movements at sarcolemma are intimately involved in the regulation of intracellular Ca2+ concentration, the present study was undertaken to test if sarcolemma plays any role to maintain cardiac function in the atrophied heart.The characteristics of sarcolemmal Ca2+ pump and Na+–Ca2+ exchange activities were examined in 8 weeks heterotopically isotransplanted rat hearts which did not support hemodynamic load and underwent atrophy. Sarcolemmal ATP (adenosine triphosphate)-dependent Ca2+ uptake and Ca2+-stimulated ATPase (adenosine triphosphatase) activities were increased without any changes in Na+–K+ ATPase activities in the transplanted hearts. Although no alterations in the Na+-dependent Ca2+ uptake were evident, Na+-induced Ca2+ release was increased in the transplanted heart sarcolemmal vesicles. The increase in Na+-induced Ca2+ release was observed at different times of incubation as well as at 5, 20, and 40 mM Na+. The sarcolemma from transplanted hearts also showed higher contents of phosphatidic acid, sphingomyelin, and cholesterol.These results indicate that increases in the sarcolemmal, Ca2+ transport activities in unloaded heart may provide an insight into adaptive mechanism to maintain normal contractile behavior of the atrophic heart.
Keywords: cardiac contractility; sarcolemmal Ca2+ pump; sarcolemmal Na+–Ca2+ exchange; membrane phospholipids; cardiac atrophy; Ca2+ transport in myocardium; transplanted heart